PENGUASAAN BUNYI BAHASA ANAK DISABILITAS TUNARUNGU USIA 10-12 TAHUN PADA KATA PASANGAN MINIMAL DI SDLB SANTI RAMA JAKARTA: SUATU KAJIAN PSIKOLINGUISTIK - Andri Asmoro (Masyarakat Linguistik Indonesia, 2016)
The sounds of language are the essence that must be mastered in human speech communication. The reality on the ground shows that there are a number of deaf children who are able to communicate verbally with normal people, despite having profound hearing obstacles and difficulties in uttering a few sounds. This experimental study attempts to explain the mastery of sounds of language that occurs in deaf children at the age 10-12 years in SDLB Santi Rama Jakarta, by using 300 words at 150 minimal pairs qualitatively. The results of analysis on phonological aspects and synthesis in this study show that deaf children actually still have the ability to perceive and produce sounds of language, although there are several obstacles in the process of mastering the sounds of language.